Water-based environmental friendly graphene-coated wearable electrically conductive textiles - Çaylak, Sena; Demirel, Onur; Javadzadehkalkhoran, Majid; Navidfar, Amir; Yaşacan, Merve; Trabzon, Levent (Springer Science and Business Media LLC, 2025)
Abstract In this study, we developed and characterized highly scalable functional e-textiles using a water-based graphene solution. Water-based graphene nanoplatelet (GNP) dispersions were prepared using sodium dodecyl benzene sulfonate (SDBS) as a surfactant and polyvinyl alcohol (PVA) as a binder, to coat the cotton fabric via a dip-pad-dry method. The results indicate a strong interaction between fibers and graphene dispersion, which leads to a tensile strength improvement of graphene-coated fabric up to 60% as compared to the pristine fabric. The sheet resistance was measured as ~ 1.9 (kΩ/sq) of the coated fabric after 7 coating cycles. Moreover, the resistance change of the graphene-coated fabric as a function of applied tensile strain was investigated. Washing tests revealed that the conductivity of the graphene-coated fabric is 10 9 times higher than that of the untreated cotton fabric, even after 7 cycles of washing. GNP has a significant effect on the thermal behavior of fabrics, which was investigated using a thermal camera during heating and cooling. Moreover, Raman spectra indicated that GNPs were integrated and adsorbed onto the fabric fibers. The SEM analysis showed that a high adhesion force between the fabric and graphene. The mechano-chemical stability, electrical and heat conductive properties of graphene-coated fabric can be used as an e-textile material for further applications. Graphical Abstract